From "this shore" to "the other shore": On Christian Culture and the Evolution of Thoughts in Chinese Confession Motif Novels in the 20th Century - CHEN, Weihua; LUO, Yilin (Journal of Research for Christianity in China (JRCC), 2025)
Since the twentieth century, the consciousness of confession in Christian culture has had a profound impact on China, which was previously considered to have no real sense of confession literature. Chinese confession motif novels are constantly changing in the changing times. Before the 1950s, it was the "introspective confession" applied to the world; in the 1970s and 1980s after the end of the "Cultural Revolution", it appeared as "complaint confession" left over from cultural trauma; since the 1990s, it gradually moved Ask the soul for "conscious remorse." From the evolution of the ideological connotation of the Chinese penitent motif novel, it can be seen that its focus has gradually shifted to the exploration of the human inner world, and the thinking about human nature has become more and more in-depth.